Antroponims Based on Religion in Old Uyghur Law Documents - Şen, Nazmi (Fırat University, 2026)
In this study, person names based on religion in old Uyghur law documents are evaluated. In short, nouns are meaningful language elements that define concrete and abstract concepts. Proper names differ from other names in that they express a single entity. A part of Old Turkish research is to analyse the origins, structures and cultural elements of the personal names found in the inscriptions and documents written on paper in that period by using various methods. There are many names of persons in documents such as loans, purchases, sales, leases, hostages, foundations, wills, exchanges, adoptions, and orders. It has been concluded that the names of people in the documents were given to people under the influence of Buddhism, ancient Turkish religion and Islam. As Buddhism has been adopted by Turkic tribes and communities since ancient times, Buddhism-oriented person names were the most common in the documents. The use of the words Kutaçuk, Kutadı, Kutadmış, Kutadmış, Kutal, Kutalmış, Kutı, Kutlug, which are based on the root Kut and kut, and the word Te?ri, which is one of the most important concepts for the ancient Turks, as a person name shows that the basic elements of the ancient Turkish religion preserve their vitality for the early Turkish society. The person names given under the influence of Islam, one of the last religions adopted in the Turfan region, are very rarely found in the documents.

Bu çalışmada, eski Uygur hukuk vesikalarındaki dine dayalı kişi adları değerlendirilmiştir. Adlar kısaca somut ve soyut kavramları tanımlayan anlamlı dil ögeleridir. Özel adlar diğer adlardan tek bir varlığı ifade etmesi bakımından ayrılmaktadır. Eski Türkçe araştırmalarının bir bölümünü o dönemde dikilmiş yazıtlarda ve kâğıda yazılı belgelerde bulunan kişi adlarının kökenlerini, yapılarını, taşıdığı kültürel ögeleri çeşitli yöntemler kullanılarak incelemek oluşturmaktadır. Borç, alım, satım, kiralama, rehin, vakıf, vasiyetname, takas, evlat edinme, buyruk türündeki vesikalarda birçok kişi adı bulunmaktadır. Vesikalardaki dine dayalı kişi adlarının Budizm, eski Türk dini ve İslamiyet etkisiyle kişilere verildiği sonucuna ulaşılmıştır. Budizm’in eski devirlerden beri Türk boy ve toplulukları tarafından benimsenmesinden dolayı vesikalarda en fazla Budizm kaynaklı kişi adları yer almıştır. Kut ve kut köküne dayanan Kutaçuk, Kutadı, Kutadmış, Kutal, Kutalmış, Kutı, Kutlug sözcükleriyle, eski Türkler için en önemli kavramlardan olan Te?ri sözcüğünün kişi adı olarak kullanılması eski Türk dinine ait temel unsurların eski Türk toplumu için canlılığını koruduğunu göstermektedir. Turfan bölgesinde benimsenen son dinlerden olan İslamiyet’in etkisinde verilen kişi adlarına vesikalarda çok az rastlanmıştır.
Eski Uygur Hukuk Vesikalarında Dine Dayalı Kişi Adları
Keywords: Language Studies (Other); Dil Çalışmaları (Diğer); Asian Cultural Studies; Asya Kültürü Çalışmaları